(untitled) (Eurasian Medical Research Periodical, 2022)
Bee products have been used by man for centuries. Numerous properties and a wide range of activity of each bee product brings the possibility of using them in the therapy of many diseases. However, more research is needed on the composition of bee products, because the mechanism of their action has not yet been fully understood. This review provides information indicating a wide range of therapeutic properties of bee venom. Numerous substances found in this venom, through various mechanisms, have beneficial and positive effects on the functioning of the human body. The most important being the protein melittin, which has a powerful anti-inflammatory action. This suggests their possible use in many medical specialties. The number of threats to honey bee is increasing all over the world, which is becoming more and more susceptible to diseases and pathogens. Bees are thought to be threatened by: bacteria, viruses, parasites, pesticides used in agriculture, environmental changes, or genetically modified organisms. Also, increasing environmental pollution contributes to the extinction of bee families, which in the future will translate into low yields